An approach to characterise spatio-temporal drought dynamics. (March 2020) - Diaz, Vitali; Corzo Perez, Gerald A.; Van Lanen, Henny A.J.; Solomatine, Dimitri; Varouchakis, Emmanouil A.
Highlights: Methods for spatial drought tracking and characterisation are presented: S-TRACK and DDRASTIC-spatial. Drought tracking involves identification of areas (clusters), centroids localisation, and centroids linkage. Drought paths are defined by an onset and an end in space and time. S-TRACK method is applied for the calculation of extreme droughts. Abstract: The spatiotemporal monitoring of droughts is a complex task. In the past decades, drought monitoring has been increasingly developed, while the consideration of its spatio-temporal dynamics is still a challenge. This study proposes a method to build the spatial tracks and paths of drought, which can enhance its monitoring. The steps for the drought tracks calculation are (1) identification of spatial units (areas), (2) centroids localisation, and (3) centroids linkage. The spatio-temporal analysis performed here to extract the areas and centroids builds upon the Contiguous Drought Area (CDA) analysis. The potential of the proposed methodology is illustrated using grid data from the Standardized Precipitation Evaporation Index (SPEI) Global Drought Monitor over India (1901-2013), as an example. The method to calculate the drought tracks allows for identification of drought paths delineated by an onset and an end in space and time. Tracks, severity and duration of the drought are identified, as well as localisation (onset and end position), and rotation. The response of the drought tracking method to different combinations of parameters is also analysed. Further research is in progress to set up a model to predict the drought tracks for particular regions across the world, including India (https://www.researchgate.net/project/STAND-Spatio-Temporal-ANalysis-of-Drought ). Graphical abstract: Image, graphical abstract